ATYPICAL FORMS OF EMPLOYMENT – A HINT OF PRECARIOUSNESS? STRUGGLING WITH THE SEGMENTATION AND PRECARISATION OF THE LABOUR MARKET (EU and comparative law issues and challenges series (ECLIC), 2020)
Creation of more and better jobs is a central issue of the ILO’s Decent Work Agenda, OECD’s jobs strategy and the European Union’s quality of work policies. While recent reports show an increase of new jobs in the European Union, the number of quality jobs is diminishing. On the other hand, there is a problematic mismatch between the education system and labour market needs. According to statistical data, Croatia is among the EU Member States with the highest rate of precarious work and the highest share of fixed-term employment in total employment. Almost a quarter of the Croatian population is at risk of poverty or social exclusion. Precarious work is closely related to non-standard or atypical forms of employment (e.g. part-time work, fixed-term employment, temporary agency work and (bogus or dependent) self-employment). These forms of employment have negative consequences for the functioning of the labour market, individual workers and the society as a whole. The authors underline shortcomings of the Croatian legislation regarding atypical forms of employment and give possible solutions that could improve the employment status and social security entitlements of those categories of workers.